The Knowledge Economy-finance nexus in SSA and MENA countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Purpose This paper assesses dynamics of the knowledge economy (KE)-finance nexus using the four variables identified under the World Bank's knowledge economy index (KEI) and seven financial intermediary dynamics of depth, efficiency, activity and size. Design/methodology/approach Principal Component Analysis is used to reduce the dimensions of KE components before dynamic panel GMM estimation techniques are employed to examine the nexuses. Findings Four main findings are established. (1) Education improves financial depth and financial efficiency but mitigates financial size. (2) But for a thin exception (trade's incidence on money supply), economic incentives (credit facilities and trade) are not consistently favorable to financial development. (3) ICT improves only financial size and has a negative effect on other financial dynamics. (4) Proxies for innovation (journals and FDI) have a positive effect on financial activity; journals (FDI) have (has) a negative (positive) effect on liquid liabilities and; journals and FDI both have negative incidences on money supply and banking system efficiency respectively. Practical Implications As a policy implication, the KE-finance nexus is a complex and multidimensional relationship. Hence, blind and blanket policy formulation to achieve positive linkages may not be successful unless policy-making strategy is contingent on the prevailing 'KE specific component' trends and dynamics of financial development. Policy makers should improve the economic incentive dimension of KE that overwhelmingly and consistently deters financial development, owing to surplus liquidity issues. Originality/value As far as we have reviewed, this is the first paper to examine the KE-finance nexus with the plethora of KE dimensions defined by the World Bank's KEI and all the dynamics identified by the Financial Development and Structure Database (FDSD).
Keywords: G21; O10; O34; P00; P48; 330; Financial development; Knowledge Economy